Toward an understanding of collaborative tax evasion: A natural field experiment with businesses - Annabelle Doerr; Sarah Necker (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2018)
Sales from businesses to consumers provide fertile ground for collaborative tax evasion. However, little is known about the phenomenon. We conduct a natural field experiment with 2,900 businesses in which we take the role of consumers and vary if we request an invoice for the delivery of a service. We find that 56% of businesses approach consumers with the intention to evade. The fraction is zero in the regulated market and 72% in the unregulated market. It increases when consumers signal their willingness to collude. Consumers can save 25% of the legal price on average if they agree to evade.
Keywords: H26; C93; E26; J22; O17; 330; collaborative tax evasion; evasion rent; field experiment